Genome-wide identification and expression analysis of the CesA/Csls gene family in Eucalyptus Grandis - An, Rui; Huang, Yingtong; Lei, Chunxia; Wu, Ai-Min; Fan, Chunjie; Long, Jianmei (Frontiers in Plant Science, 2025)
IntroductionThe cellulose synthase gene superfamily is composed of two major gene families: cellulose synthase (CesA) and cellulose synthase-like (Csl). These genes play a crucial role in the synthesis of cellulose and hemicellulose within the plant cell wall, and are essential for controlling plant growth and development. However, the CesA/Csls gene family has not been previously reported in Eucalyptus grandis.MethodsIn this study, bioinformatics methods were employed to identify the CesA/Csls gene family inE. grandisand to analyze the potential functions of its members in cell wall formation.ResultsThe results revealed that there were 62 CesA/Csls family members inE. grandis, which were classified into seven subfamilies (CesA, CslA, CslB, CslC, CslD, CslE, CslG) based on evolutionary tree analysis. Promoter regions of these genes contained various cis-acting elements, with light-responsive elements being the most abundant. Gene expression pattern analysis showed that EgCesA4, EgCesA7, and EgCesA8 were highly expressed in the xylem, suggesting their primary association with cellulose synthesis during secondary wall thickening (lignification).DiscussionOverall, the analysis of the EgCesA/Csls gene family provides a valuable reference for understanding cellulose synthesis in the cell wall, genetic improvement, and biotechnological applications.